2006
DOI: 10.1111/j.1530-0277.2006.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Versus Daily Naltrexone: Secondary Analysis of Effects on Average Daily Drinking

Abstract: Although in both genders, targeted treatments appeared to reduce the volume of drinking, treatment with targeted naltrexone was somewhat better. In contrast, heavy drinking women showed no benefit from daily naltrexone treatment. Further evaluation of the efficacy of targeted treatments and of daily naltrexone and the relationship of these treatments with gender is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 13 publications
2
66
1
1
Order By: Relevance
“…The primary analysis strategy consisted of six separate zero-inflated Poisson (ZIP) regression models to examine predictors of participantto-partner aggression (psychological-, physical-, injury-) and partner-to-participant aggression (psychological-, physical-, injury-). ZIP regression is appropriate to use with event count data (i.e., data composed of the total number of counts of a specified behavior within a given time period), particularly event data in which the possibility exists for a large number of 0 scores (Zorn, 1996;Hernandez-Avila, 2006). Given that our outcome measures involved event count data for aggression, ZIP regression is the most appropriate approach to account for the large number of zeros.…”
Section: Discussionmentioning
confidence: 99%
“…The primary analysis strategy consisted of six separate zero-inflated Poisson (ZIP) regression models to examine predictors of participantto-partner aggression (psychological-, physical-, injury-) and partner-to-participant aggression (psychological-, physical-, injury-). ZIP regression is appropriate to use with event count data (i.e., data composed of the total number of counts of a specified behavior within a given time period), particularly event data in which the possibility exists for a large number of 0 scores (Zorn, 1996;Hernandez-Avila, 2006). Given that our outcome measures involved event count data for aggression, ZIP regression is the most appropriate approach to account for the large number of zeros.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cognitive effects of acute and chronic NTX may differ, recent data supports equivalent or greater efficacy of acute NTX dosing, relative to daily maintenance, in reducing excessive alcohol intake (Hernandez-Avila et al, 2006). Thus, determining the cognitive effects of acute NTX doses is warranted.…”
Section: Discussion Ntx Effects On Impulsive Choicementioning
confidence: 99%
“…NTX reduces alcohol consumption, craving, and relapse in subjects with a history of alcohol abuse (O'Brien et al, 1996;Anton et al, 1999;Davidson et al, 1999;Hernandez-Avila et al, 2006;see Heidbreder, 2005 for a recent review). Moreover, NTX significantly reduces ethanol consumption in rats (Stromberg et al, 1998) and monkeys (Boyle et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating data have suggested that men and women with alcohol or drug dependence can respond differently to the same pharmacological treatment, typically with men having better treatment outcomes than women (Garbutt et al, 2005;Hernandez-Avila et al, 2006;Pettinati, Dundon, & Lipkin, 2004). However, at least one naltrexone study has suggested that alcohol-dependent women treated with 50mg/day of naltrexone abstained from alcohol for a longer duration than men (Kiefer, Jahn, & Wiedemann, 2005).…”
Section: Introductionmentioning
confidence: 99%